Penatalaksanaan Fisioterapi Pada Kasus Tuberkulosis Paru Di RSP. Ario Wirawan Salatiga - NOORHIDAYAH, Dwi (2015)
Background Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. Pulmonary tuberculosis is tuberculosis that attacks the lungs but can also spread to other body parts, including meningitis, kidney, bone, and lymph nodes. Mycobacterium tuberculosis is acid-resistant aerobic rods that grows lowly and are sensitive to heat and ultraviolet rays. Problematic physiotherapy obtained their sputum and shortness of breath. Methods : the method used is giving lip pulse and breathing exercises effective coughing exercises are evaluated by using at able lay out for their sputum and Borg scale for the degree of shortness of breath. Objectives : the above method to determine the purpose of the pulse lip breathing exercises and coughing exercises effective against their sputum and shortness of breath. Results :6 times after start of therapy showed the disappearance of sputum and reduced the degree of breathlessness. Conclusion :Giving pulse lip breathing exercises and coughing exercises can effectively reduce their sputum and shortness of breath.